ANALISIS PENERAPAN TOTAL QUALITY MANAGEMENT (TQM) INDUSTRI PERTAHANAN NASIONAL (Studi kasus pada Industri Senjata) - Yusuf Novrianto; Rudy Soenoko; Purnomo Budi Santoso (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2014)
Military weapons industries supporting industries most likely to be developed into a leading center of technology in accordance with the type of industry. With that goal achieved through Total Quality Management is an approach oriented to continuous quality improvement. Based on this analysis needs to be done related to the components of total quality management what are the qualities that support the quality of production and how its application in the arms industry and how to identify one component of total quality management that affect the quality improvement of quality related to changes in the occurrence of downtime in production with the method klongsong MVSM. On the basis of the proposed theoretical model, the analysis of corporate performance, descriptive analysis and analysis of TQM. TQM implementation is based on customer focus, obsession with quality, scientific approach, long-term commitment, teamwork, continuous improvement systems, education and training, unity of purpose, as well as the involvement and empowerment of employees